Preparation of PtNi@SDC core-shell nanoparticles by one-pot solvothermal synthesis - Quek, Kenneth Kai Wen (Nanyang Technological University, 2021)
In this study, fabrication and characterization of platinum-nickel (PtNi) nanoparticles by one-pot solvothermal synthesis was undertaken. Using different surfactant concentrations and solvothermal synthesis durations, their effects on the fabricated nanoparticles were studied. Annealing of the nanoparticles at 450, 600 and 800 °C was then performed to test their thermal stabilities, and characterization techniques were applied to analyse the morphologies of the nanoparticles before and after annealing. It was found that using higher surfactant concentrations resulted in larger PtNi nanoparticles, and increasing the solvothermal duration also caused an increase in nanoparticle size, although this effect was less obvious at lower surfactant concentrations. A composite relationship between surfactant concentration and solvothermal duration to the elemental composition of the PtNi nanoparticles was also identified. With increasing surfactant concentration and solvothermal duration, the percentage of platinum in the nanoparticles decreased. Thermal stability of the nanoparticles was found to be the combined effect of particle size and elemental composition, where larger particles with the elemental composition closer to a ratio of 1:1 platinum-to-nickel presented higher thermal stabilities. It was concluded that the nanoparticle sample prepared with 50 mM surfactant concentration and 18 hours solvothermal synthesis duration possessed the best combination of thermal stability, particle size and elemental composition. Therefore, it was used as the cathode material for the fuel cell polarization test, and also as the core in the hydrothermal synthesis of platinum-nickel core, samaria-doped ceria shell (PtNi@SDC) nanoparticle catalyst. The polarization test at 450 °C measured a maximum power density of 0.12 mW cm-2 at a current density of 0.27 mA cm-2. Fabrication of the PtNi@SDC core-shell nanostructure was however, unsuccessful, which was possibly due to the high polarity of the solvent used. This caused discrete ceria particles to be formed among the PtNi nanoparticles. Other solvents with lower polarity could be applied in a future study to fabricate the PtNi@SDC core-shell nanoparticles.